TANGGAPAN EKSEKUTIF DAN LEGISLATIF DI PEMERINTAH PROVINSI DAERAH ISTIMEWA YOGYAKARTA DALAM IMPLEMENTASI PERATURAN PRESIDEN NO. 5 TAHUN 2006 TENTANG KEBIJAKAN ENERGI NASIONAL (Studi Kasus Implementasi Kebijakan Pengembangan Energi Alternatif di Provinsi Daerah Istimewa Yogyakarta) - , Romi Ardiansyah, Dr. Phil. Gabriel Lele, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research originated when then government issued the Presidential Regulation no.5 in the year of 2006 about the National Energy Policy (NEP). The Presidential Regulation no.5 in the year of 2006 accommodates the goal of the government wants to be achieved in the year of 2025 related with energy management. One of the important parts on that policy is the energy utilization transition from fossil fuel into optimizing the energy alternative as well as renewable or nonrenewable resources. According to the definition, alternative energy sources especially the stock of renewable energy in different local area around Indonesia is plenteous such as water energy, wind energy, sea wave energy, solar energy and biomass energy. This research is focused to seek the respond of both executive and legislative DIY Provincial Government through the implementation of the Presidential Regulation no.5 in the year of 2006 especially in the context of alternative energy. This research uses the descriptive method with the qualitative approach. By this method, it expected that will give the completely view how the executive and legislative in the DIY provincial government respond to the implementation of the Presidential Regulation no.5 in the year of 2006 about the National Energy Policy especially in the aspect of alternative energy development. From this research can be concluded that the executive and legislative in the DIY provincial government respond to the implementation of the Presidential Regulation no.5 in the year of 2006 about the National Energy Policy especially in the aspect of alternative energy development still weak. This weak response happened because of some causes such as the legislative and executive do not really understood about the policy, there is no legal law about energy development in the other local area, also the minimum allocation budget on the energy sector of DIY province. This weak respond cause the development of alternative energy in DIY become slow. For the future year, it needs more socialization and discussion between the executive and legislative side that can made the policy could be understood for both. Optimizing development of alternative energy in DIY need to be more powerful by made the energy development as the main priority of local area development. To ensure the energy development sustainability in the local area need to have the global plan that can be written as the local regulation